2019
DOI: 10.3390/molecules24050830
|View full text |Cite
|
Sign up to set email alerts
|

Weinreb Amides as Directing Groups for Transition Metal-Catalyzed C-H Functionalizations

Abstract: Weinreb amides are a privileged, multi-functional group with well-established utility in classical synthesis. Recently, several studies have demonstrated the use of Weinreb amides as interesting substrates in transition metal-catalyzed C-H functionalization reactions. Herein, we review this part of the literature, including the metal catalysts, transformations explored so far and specific insights from mechanistic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 134 publications
(146 reference statements)
0
29
0
Order By: Relevance
“…A similar yield was obtained when Me 4 NOAc (1 equiv.) was added (entry 3), while other quaternary ammonium salts gave inferior results (entries [4][5][6][7][8][9][10][11]. Control experiments have shown that no reaction occurred in the absence of rhodium catalyst or molecular oxygen (entry 12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar yield was obtained when Me 4 NOAc (1 equiv.) was added (entry 3), while other quaternary ammonium salts gave inferior results (entries [4][5][6][7][8][9][10][11]. Control experiments have shown that no reaction occurred in the absence of rhodium catalyst or molecular oxygen (entry 12).…”
Section: Resultsmentioning
confidence: 99%
“…C-H functionalization, including the reaction of a C-H bond with a (pseudo)halide, the reaction of a C-H bond with an organometallic reagent, and cross-coupling between two C-H bonds (CDC reaction), has gained tremendous popularity in recent years as a methodology for the construction of C-C bonds or C-heteroatom bonds [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Among these reactions, the CDC reaction is especially noteworthy because this reaction precludes both coupling partners from pre-functionalization, and as a result has high step economy and atom economy [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there are few related comments in this field. In 2016, Yu's group used a large number of examples to comment and summarize the C–H activation reaction using N ‐methoxyamide as a versatile directing group; In 2017, Kapur and co‐workers published a review on the proximal C–H functional groups of aromatic amides and anilines using amides as weak coordination groups; In 2019, the Pilarski team summarized Weinreb amide‐directed C–H functionalization from the perspective of catalyst and mechanism . However, in the few examples mentioned above, the scope of coverage is relatively narrow, either to comment on the functionalization of a specific directing group or to summarize the functionalization of a specific reaction site.…”
Section: Introductionmentioning
confidence: 99%
“…The reports on the Pd(II)‐catalyzed aryl C−H alkenylation for late stage functionalization to generate analogs of the COX‐2 selective anti‐inflammatory drug celecoxib, [8] the Ru(II)‐catalyzed aromatic ring alkenylation [9] via C−H activation directed by the oxazolidinone heterocycle, essential pharmacophoric feature of diverse therapeutic agents, [10] and the late‐stage arylation of pharmaceuticals by cyclo‐metallated ruthenium catalyst [11] caught our attention. Furthermore, assistance of directing groups (DGs) [4a–i] are required for C−H activation to enhance the selectivity and reactivity but often the pendant DG is not required in the product. Thus, the incorporation of the DGs and their post C−H activation removal require additional synthetic steps undermining the proclaimed step‐economical advantage of the C−H activation strategy.…”
Section: Introductionmentioning
confidence: 99%